RESPON TANAMAN KACANG HIJAU ( Vigna radiate L. ) TERHADAP JENIS DAN DOSIS PUPUK ORGANIK - Astri Sumiati; Edison Indawan; Poppy Indrihastuti; Yohanes Aryanto Dendo Ngara (Universitas Tribhuwana Tunggadewi, 2021)
The purpose of this research was to study the effectiveness of type and dose of organic fertilizer on the growth and yield of green beans. The method used in this research was a completely randomized design of a factorial pattern. The factors consisted of a type of organic fertilizer (J) (J1 = chicken manure, J2 = cow manure, J3 = bokashi municipal waste) and the dose of organic fertilizer (D) (D1 = 80 g/polybag, D2= 160 g/polybag, D3= 240 g/polybag). The results showed that there was no interaction between the type and dose of organic fertilizer on all observation parameters. Organic fertilizer type bokashi municipal waste was gave an effect on the parameters of plant height at the age of 42 DAP (53 cm), the number of leaves at the age of 42 DAP (23.23 strands). The dose of 80 g/polybag gave a significant effect on plant height parameters at 42 DAP (53 cm), the number of leaves at 42 DAP (23.22 strands).